Light-triggered polymeric prodrug and nano-assembly for chemo-photodynamic therapy and potentiate immune checkpoint blockade immunotherapy for hepatocellular carcinoma. (January 2023) - Gao, Yang; Su, Zhe; Wang, Cui; Xu, Jianjun; Hu, Shaobo; Zhang, Chen; Sun, Ping; Zhou, Xing; Wang, Weimin; Zou, Tianhao; Yang, Bing; Cheng, Xiang; et al.
Graphical abstract: Highlights: A prodrug nanoplatform was synthesized for drug delivery and light-triggered release. The micelles mediated chemo-photodynamic therapy could elicit antitumor immunity. Micelles combined with Immune checkpoint blockade (ICB) could effectively inhibit primary and distant lesions. Abstract: Immune checkpoint blockade (ICB) therapy has emerged as a promising approach for the treatment of hepatocellular carcinoma (HCC), especially for advanced and metastatic tumors. However, many HCC patients do not respond due to low tumor antigen exposure and the highly immunosuppressive tumor microenvironment (ITM). Chemotherapy and photodynamic therapy are considered to be effective methods for eliciting anti-tumor immune responses. Here, we developed a light-triggered nanoplatform Ce6@PMTKP for combination chemo-photodynamic therapy and the potentiation of ICB therapy. The Ce6@PMTKP micelles entrapped Ce6 for photodynamic therapy, while PMTKP contains the ROS-sensitive paclitaxel (PTX) polymeric prodrug for chemotherapy. The Ce6@PMTKP micelles showed excellent tumor accumulation and light-triggered drug release. Compared with chemotherapy or photodynamic therapy alone, the combination therapy mediated by Ce6@PMTKP was found to be more effective in the elimination of tumors, induction of immunogenic cell death, and the promotion of dendritic cell maturation and cytotoxic T lymphocytes infiltration, thus mitigating ITM immunosuppression. When combined with anti-PD-L1 immunotherapy, the Ce6@PMTKP micelles induced complete regression of primary tumors and effectively inhibited distant metastatic tumors by enhancing anti-tumor immune responses.